Dyskusja programowa na łamach czasopism Międzyzakładowego Komitetu Założycielskiego i Zarządu Regionu Wielkopolska NSZZ "Solidarność" w latach 1980-1981 - Brzechczyn, Krzysztof (Instytut Pamięci Narodowej, 2016)
This article analyses the programme discussion in the trade union’s press supported by the trade union’s regional structures: the Inter-Enterprise Founding Committee, and subsequently the Wielkopolska Regional Board of the Independent Self-Governing Trade Union “Solidarność”. The press of „Solidarność” in the Wielkopolska region is distinguished by two groups of articles: reprints from other independent papers and first-time published articles. This article only interprets the latter group of publications. Those articles mainly focused on dominant topics such as discussions on the trade union’s current programme and its organization, the economic reform, the preparation to local self-government elections and the trade union’s global strategy.
Keywords: Solidarność; myśl polityczna; historia Polski; historia Wielkopolski; Solidarity; historia opozycji